Differential profiles of autophagy and Nrf2-mediated antioxidant response in HBeAg-positive versus HBeAg-negative chronic hepatitis B patients - Liu, Pei; Tang, Yuna; Wang, Jing; An, Qi; Zhang, Ying; Wei, Xuefei; Cui, Chao; Fan, Yuchen; Liu, Huihui; Wang, Kai (Frontiers in Microbiology, 2025)
BackgroundHBeAg (hepatitis B e antigen) seroconversion is a key focus in the current treatment of chronic hepatitis B. The processes of autophagy and oxidative stress has been found to be involved in HBV replication and translation. It remains unclear whether this process plays a promotive or inhibitory role in HBeAg seroconversion.MethodsThis study aims to evaluate the role of autophagy in disease progression by quantifying Beclin1 and P62 (Sequestosome 1) as indicators of autophagic activity in hepatitis B patients. Additionally, the Nrf2-Keap1 pathway (nuclear factor erythroid 2-related factor 2/Kelch-like ECH-associated protein 1) serves as a marker of antioxidant defense capacity, thereby allowing an assessment of the contribution of oxidative stress to the progression of the disease in these patients. We examined the expression patterns of these factors in peripheral blood mononuclear cells (PBMCs) and plasma from both HBeAg -positive and HBeAg-negative groups (n = 234) using quantitative real-time polymerase chain reaction (RT-qPCR) and ELISA.ResultsThe expression levels of Beclin1 and Keap1 were significantly increased compared to those in the HBeAg-negative group (P < 0.05). The expression levels of P62, Nrf2, GSH (Glutathione), GSTs (Glutathione S-transferases), and Ho-1 (Heme oxygenase) were significantly decreased compared to those in the HBeAg-negative group (P < 0.05). In the HBeAg (+) subgroup stratified by median levels of Beclin1, Nrf2, and Keap1, comparative analysis revealed statistically significant differences in alanine aminotransferase (ALT) expression between Beclin1-high and Beclin1-low groups (P < 0.05). Specifically, the Beclin1-high group exhibited significantly higher ALT levels compared to the Beclin1-low group. In the Keap1-stratified analysis, total bilirubin (TBIL), direct bilirubin (DBIL), and indirect bilirubin (IBIL) showed statistically significant differences (P < 0.05), with elevated bilirubin levels observed in the Keap1-high group. Further analysis within the HBeAg (+) subgroup demonstrated significant differences in aspartate aminotransferase (AST), DBIL, and alpha-fetoprotein (AFP) expression between Nrf2-high and Nrf2-low groups (P < 0.05). The Nrf2-high group displayed higher AST and DBIL levels but lower AFP levels compared to the Nrf2-low group.ConclusionBased on our findings, we conclude that autophagy and the Nrf2-Keap1 antioxidant signaling pathway play critical roles in the process of HBeAg seroconversion in chronic hepatitis B patients. Furthermore, monitoring ALT/bilirubin dynamics (linked to autophagy/oxidative stress) may assist in treatment optimization, supporting the quest for clinical cure.